Concise Review On Daily Regimen Modification To Attain Good Quality Life W.S.R. To Mother And Child Health Care - Sharma, Aakanksha; Parashar, Rahul; Mishra, Pramod; Sharma, Vijay Bhushan (International Research Journal of Ayurveda & Yoga, 2020)
Our country is home to the largest child population in the world. We know that generally, a child who enjoys a better state of health during childhood will become a healthy adult. So, we need a more concrete and compassionate road map to ensure that every child is safe and protected. Ayurvedic daily regimen (Dincharya) is one of the most powerful preventive measure to ensure a long and healthy life for humans. Dincharya is a gift for the people and children to live healthy and longer. In the assimilation of Ayurvedic daily regimen (Dincharya) in the life of child (Ksheerap and Ksheerannad) their mother can play an important role. A mother can greatly influence child’s growth and development by applying all regimen on her child like Abhyanga (oil massage), Anjan (collyrium), Snaana (bath), Pratimarsha-Nasya (nasal drop) etc. can be applied to the baby by the mother.